Increasing energy efficiency in passenger ships by novel energy conservation measures. Issue 2 (4th May 2018) - El Geneidy, Rami; Otto, Kevin; Ahtila, Pekka; Kujala, Pentti; Sillanpää, Kari; Mäki-Jouppila, Tero
ABSTRACT: To achieve increasing emission requirements, the cruise ship industry is working to develop higher efficiency ships. Cruise ships are different from other ship types in their relatively higher consumption of electrical power, steam and hot water. Several novel high-efficiency system concepts are possible for on-board electrical power generation and other utility services, each with differing impacts and first costs. Low-emission concepts novel to the cruise ship industry include combinations of exhaust gas heat recovery, heat pumps, steam turbines and organic Rankine cycles (ORCs). Yet, evaluation of these concepts is difficult given the different operating modes of cruises, and overall efficiency is dependent on the dynamic operational sequences. In this paper, we compare alternative energy efficiency concepts for cruise ships through simulation studies of the ship operations when equipped with different novel power generation systems. We find that the dual pressure steam systems and ORC offer the greatest potential for energy efficiency improvements in the cruise ship industry. We also find that relatively conventional technologies enable cruise ships to comply with planned upcoming higher ship energy efficiency requirements.